ANALISIS YURIDIS TERHADAP PENYELESAIAN KONFLIK PERTANAHANDI AREAL TANAH GARAPAN (STUDI DI KANTOR PERTANAHAN KABUPATEN LANGKAT) - NATALRIA ARGENTINA BR SURBAKTI (PREMISE LAW JURNAL, 2014)
ABSTRACT   This is an analytical descriptive empirical juridical study to analyze the data obtained through field research related to the specific theory of law related to agrarian law. Through this study, the problems found in the field were explained and analyzed then a conclusion was drawn to be the solution to problems. The data analysis was conducted by concluding the primary and secondary data which then were evaluated and qualitatively analyzed to discuss the problems based on the data found in the field and the regulations of legislation related to the agrarian law to obtain new description or to strengthen the existing description in answering the problems and drawing a conclusion as well as beneficial suggestions. Land conflict in Langkat District occured due to the factors of lack of knowledge and legal awareness and unfavorable behavior due to the high dependence on land in meeting the daily life necessities in the community in Langkat District. The settlement of the conflict occured in Langkat District was done through mediation at the Langkat District Land Office and if this mediation failed the conflict settlement was usually continued to be sttled through litigation (court of law). Keywords: Land Conflict, Land Office, Langkat District